Everyday Life Emotions during Anti-Fugitive Offenders Ordinance Protests in Hong Kong - Ma, Tsz-Wah (European Journal of Mental Health, 2020)
This experience sampling study investigated the impact of political movement (i.e. Anti-Fugitive Offenders Ordinance Protests) on everyday emotional reactivity and dynamics. Participants who finished our experience sampling during Movement (18–70 years; n = 100) and matched sample (18–70 years; n = 100) reported positive and negative emotions seven times a week for five weeks. Hierarchical linear modeling revealed that during the Movement, participants reported lower positive emotions and higher negative emotions, and lower positive emotional inertia and higher nega - tive emotional inertia. This study is the first of its kind to investigate different aspects of everyday emotional experiences during political movements. Participants perceived significant changes in their everyday events although the Movement was not long and not severely violent. This study highlights the importance of investigating everyday emotions of people in other more serious conflict and post-conflict settings.